Rate of 6-[18F]fluoro-L-dopa uptake decline in striatal subregions in Parkinson’s disease - Gallagher, Catherine L (2011)
Using both a volume of interest (VOI) and whole brain voxel-wise approach, we compared rates of decline of 6-L-[(18)F]-fluorodopa (FDOPA) positron emission tomography (PET) uptake ipsilateral (IL) and contralateral (CL) to the initially symptomatic limbs over 4.5 years in 26 subjects with Parkinson’s disease (PD) and 11 controls. The VOI approach used six subregions: Head/body of caudate nucleus, whole putamen, and posterior putamen. The absolute rate of decline in PD was significantly greater than in controls in all subregions, but did not differ significantly by region. Ratios of uptake between regions did not change during the study with the exception of the IL putamen/caudate ratio. Both male gender and advancing age were associated with lower baseline FDOPA uptake in PD, but no difference in decline rates. In the PD group, decline rates were marginally greater during earlier time segments. Striatal FDOPA uptake was significantly correlated with disease duration and with progression of time during the study, but only moderately correlated with UPDRS scores. We conclude that FDOPA uptake in subregions of the striatum is strongly correlated with disease duration and age, and declines equally from symptom onset in PD. This implies that in idiopathic PD, relative preservation of uptake in the anterior striatum reflects a delay in pathologic involvement of nigrostriatal projections to these regions.